Beneficial Influence of Agomelatine Treatment on Behavioral Impairments in AΒ-Induced Rat Model of Alzheimer’s Disease - Kalina Ilieva; Jana Tchekalarova; Milena Atanasova; Lidiya Petrova (Journal of Biomedical & Clinical Research)
An increased risk of developing Alzheimer’s disease (AD) exists in patients with a history of depression. In the present study, we demonstrated that chronic agomelatine intraperitoneal treatment, at a dose of 40 mg/ kg for 21 days, starting one month after inducing AD by intracerebroventricular injection of amyloid-beta (Aβ) corrected anhedonia, decreased anxiety, and showed a potential to mitigate working memory errors during the last session in a radial arm maze. Altogether, our findings suggest that chronic agomelatine administration treatment could alleviate the burden of AD and may be considered a promising therapeutic approach to some adverse symptoms caused by the disease.